P2X4 purinergic receptors offer a therapeutic target for aggressive prostate cancer. Issue 2 (25th November 2021) - Maynard, Janielle P; Lu, Jiayun; Vidal, Igor; Hicks, Jessica; Mummert, Luke; Ali, Tamirat; Kempski, Ryan; Carter, Ayanna M.; Sosa, Rebecca Y; Peiffer, Lauren B; Joshu, Corinne E; Lotan, Tamara L; et al.
Abstract: Prostate cancer (PCa) remains a leading cause of cancer‐related deaths in American men and treatment options for metastatic PCa are limited. There is a critical need to identify new mechanisms that contribute to PCa progression, that distinguish benign from lethal disease, and that have potential for therapeutic targeting. P2X4 belongs to the P2 purinergic receptor family that is commonly upregulated in cancer and is associated with poorer outcomes. We observed P2X4 protein expression primarily in epithelial cells of the prostate, a subset of CD66 + neutrophils, and most CD68 + macrophages. Our analysis of tissue microarrays representing 491 PCa cases demonstrated significantly elevated P2X4 expression in cancer‐ compared with benign‐tissue spots, in prostatic intraepithelial neoplasia, and in PCa with ERG positivity or with PTEN loss. High‐level P2X4 expression in benign tissues was likewise associated with the development of metastasis after radical prostatectomy. Treatment with the P2X4‐specific agonist cytidine 5′‐triphosphate (CTP) increased Transwell migration and invasion of PC3, DU145, and CWR22Rv1 PCa cells. The P2X4 antagonist 5‐(3‐bromophenyl)‐1, 3‐dihydro‐2H‐benzofuro[3, 2‐e]‐1, 4‐diazepin‐2‐one (5‐BDBD) resulted in a dose‐dependent decrease in viability of PC3, DU145, LNCaP, CWR22Rv1, TRAMP‐C2, Myc‐CaP, BMPC1, and BMPC2 cells and decreased DU145 cell migration and invasion. Knockdown of P2X4 attenuated growth, migration, and invasion of PCa cells. Finally, knockdown of P2X4 in Myc‐CaP cells resulted in significantly attenuated subcutaneous allograft growth in FVB/NJ mice. Collectively, these data strongly support a role for the P2X4 purinergic receptor in PCa aggressiveness and identify P2X4 as a candidate for therapeutic targeting. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.